EFEKTIVITAS PENGGUNAAN PLATFORM DIGITAL SELAMA PANDEMI COVID-19 DI SDIT NURUL ANSHAR SITUBONDO - Kaulika, Syamela Massa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
A series of learning activities carried out online-based, in order to reduce the spread of covid 19. The use of online media also has an impact on the effectiveness of the learning carried out. Therefore, it is necessary to pay attention to the achievement of online learning objectives. This study aims to identify the level of effectiveness of the use of online learning media carried out during a pandemic in the moral creed lessons at SDIT Nurul Anshar Situbondo, through a quantitative research approach. Data collection techniques using observation, interviews, and questionnaires were distributed to fifth grade students at SDIT Nurul Anshar using a Likert scale. Due to the limitations of existing students, the researcher used three classes at once with a random sampling technique. Data analysis techniques using statistics. Based on the results of the research that has been carried out, it says that online learning carried out during a pandemic at SDIT Nurul Anshar is running well and effectively. this is also supported by technology, online learning media, time efficiency, the character of students and teachers is also considered with the result that online learning can be continued and learning material is conveyed properly to students.